Pengaruh Pemasaran Terhadap Minat Pelanggan di PT. An-Nur Ma'arif (Faza Tour) Palembang - Yopi Salendra; Nuraida Nuraida; Hasril Atieq Pohan (Social Science and Contemporary Issues Journal, 2023)
Research entitled Marketing Influence of PT. An-Nur Maarif (Faza Tour) Palembang Against Customer Interests. With the aim of research to determine the marketing influence of PT. An-Nur Maarif (faza tour) Palembang on customer interest. With the research methodology used quantitative, data collection techniques through observation, questionnaires and documentation. Data analysis techniques include validity test, reliability test, normality test, linearity test, multiple linear test and hypotheses. The results of the research are based on the data analysis carried out by writing, it is known that the value of t = 23,445 while the sig value is 0.020. The small sig value of the significance value is 0.05, this means that there is a significant influence between the marketing variable (X) on the customer interest variable (Y). Partially obtained the value of t count 2.466 > 2.0484 (see ttable) so it can be concluded that H1 is accepted and Ho is rejected, meaning that there is a marketing influence of PT. An-Nur Maarif (Faza Tour) Palembang on customer interest. In the R Square column, a value of 0.952 is obtained, this shows that it has an influence of 95% on marketing influence.